La Motivación en el Rendimiento de Talento Humano en el Seguro Social Campesino en el cantón Pastaza - De La Torre Cherres, Johnn Ayrton (2025)
The present research centred on the issue of demotivation and low performance among human resources at the Seguro Social Campesino (Rural Social Security) in Pastaza. This situation was causing negative impacts on operational efficiency and the quality of the services provided, affecting both employees and the beneficiaries of the institution’s services. The objective was to analyse the influence of motivation on the performance of the institution’s personnel, involving a diagnosis of the current motivational situation, the identification of the relationship between motivation and performance, and the proposal of strategies to improve both aspects. The methodology adopted was descriptive and non-experimental, employing tools such as surveys and statistical analyses, including Pearson correlation and Chi-Square tests, to evaluate staff motivation and performance. The results revealed a significant correlation between work motivation and the performance of human resources, and critical factors influencing motivation were identified, such as recognition and opportunities for professional development. Based on these findings, strategies were proposed that focused on improving recognition, fostering professional development, and enhancing effective communication to boost motivation and, consequently, staff performance